2014
DOI: 10.1021/jp504377r
|View full text |Cite
|
Sign up to set email alerts
|

Critical Electron Transfer Rates for Exciton Dissociation Governed by Extent of Crystallinity in Small Molecule Organic Photovoltaics

Abstract: Solution-processed bulk heterojunction organic solar cells fabricated with 1,3-bis[4-( N,N -diisopentylamino)-2,6-dihydroxyphenyl]squaraine and phenyl-C61-butyric acid methyl ester were found to exhibit unexpectedly low external quantum efficiency in the squaraine regions upon annealing. X-ray diffraction (XRD), spectral response, and time-resolved microwave absorption were all used to characterize the materials used and the devices prepared from them. An explanation for the drop in efficiency is proposed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…It has been reported that improving crystallinity of the SQ films by thermal annealing [35,45] and solvent annealing [36] results in an optimized solar cell performance. Our group has found a decrease in the device efficiency after thermal annealing [20] and, in this case, we assign this to the significant SQ:PC 61 BM phase separation at high annealing temperatures. The domain size after phase separation is estimated to be 50-200 nm in diameter according to the TEM images (Fig.…”
Section: Organic Photovoltaic Devicesmentioning
confidence: 56%
See 2 more Smart Citations
“…It has been reported that improving crystallinity of the SQ films by thermal annealing [35,45] and solvent annealing [36] results in an optimized solar cell performance. Our group has found a decrease in the device efficiency after thermal annealing [20] and, in this case, we assign this to the significant SQ:PC 61 BM phase separation at high annealing temperatures. The domain size after phase separation is estimated to be 50-200 nm in diameter according to the TEM images (Fig.…”
Section: Organic Photovoltaic Devicesmentioning
confidence: 56%
“…We consider the following explanation based on our accurate assignment of the excited states. The "dark" state lying below the two "bright" H-states will be populated through Kasha's rule relaxation and these resulting lower energy excitons will likely dissociate with a reduced probability given their lower energy levels relative to the PC 61 BM LUMO, described in part by Marcus Theory [20,46]. In previous studies of squaraine materials in OPV devices, the same strategies employed to optimize solar cells, such as thermal annealing, do not always lead to the same resulting device efficiency.…”
Section: Organic Photovoltaic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, once the theory for the excited states is completely 3 and precisely determined, squaraines can be used as robust and predictable mechanistic probes for a better, consistent and fruitful understanding of the universal OPV device. 13 Furthermore, once the structure-function connection between excited states and device efficiency has been made, then squaraines can be prescriptively functionalized, or tuned, for processing in non-toxic solvents, ready for mass production. 10 In order to recognize predictable trends in squaraine tunability, we can describe the behavior of each member of a small series, assigning the spectra as the squaraines interact with each other in a range of different environments spanning dilute liquid solution, (completely isolated molecules), concentrated solid solutions (through work with polymethylmethacrylate films), nanoparticle dispersions in mixed solvents, and in neat and blended films (analogous to active layers for OPV devices).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have long been used for mimicking photosynthetic light-harvesting antennas [2] [3] [4] [5]. Due to the remarkable optical and transport properties, J-aggregates have also shown great promise in color photography [6], nonlinear optics [7] [8], light emitting diodes [9] [10], and solar cells [11] [12]. However, the application of J-aggregates in biosensors is still limited [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%